1999
DOI: 10.1016/s0928-8244(98)00114-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cigarette smoke on adherence of respiratory pathogens to buccal epithelial cells

Abstract: Smoking is associated with an increased risk of respiratory tract infection in adults. In children, exposure to cigarette smoke is a risk factor for respiratory tract infection and bacterial meningitis: Active smoking and passive exposure to cigarette smoke is also associated with carriage of some potentially pathogenic species of bacteria in both adults and children. The aims of the study were to determine the effect of active smoking on: (1) bacterial binding to epithelial cells; (2) expression of host cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 7 publications
1
28
0
Order By: Relevance
“…50 51 This could possibly be the result of a direct effect of cigarette smoke on host defences since smoking is negatively associated with cell mediated and humoral immunity, and smoking increases bacterial adherence and the risk of inflammation and other infections. [52][53][54][55] The observation that smokers are more likely to be carriers of meningococci is consistent with the increased risk of invasive meningococcal disease. 56 Middle ear disease and adenotonsillectomy in children In a systematic quantitative review, Strachan and Cook concluded that there is probably a causal relation between parental smoking and both acute and chronic middle ear disease in children.…”
Section: Infectionssupporting
confidence: 53%
“…50 51 This could possibly be the result of a direct effect of cigarette smoke on host defences since smoking is negatively associated with cell mediated and humoral immunity, and smoking increases bacterial adherence and the risk of inflammation and other infections. [52][53][54][55] The observation that smokers are more likely to be carriers of meningococci is consistent with the increased risk of invasive meningococcal disease. 56 Middle ear disease and adenotonsillectomy in children In a systematic quantitative review, Strachan and Cook concluded that there is probably a causal relation between parental smoking and both acute and chronic middle ear disease in children.…”
Section: Infectionssupporting
confidence: 53%
“…Exposure to cigarette smoke has been associated with abnormal mucosal development in children [66]; mucosal immune dysregulation in infants [67]; airway irritation that can result in local epithelial damage [68, 69]; airway inflammation which can adversely affect mucocilliary clearance [69, 70]; increased risk of carriage of potentially pathogenic bacteria [71] and dental caries [72] in children. Higher mucosal IgA levels in the infants of smokers have been attributed to more chronic upper RT symptoms [32, 33] which may be associated with increased adherence of respiratory pathogens to buccal epithelial cells [73]. In our study cohort, exposure to ETS was associated with elevated salivary IgA and IgG concentrations.…”
Section: Discussionmentioning
confidence: 69%
“…It is common for a family, often including members of the extended family, to live together in a traditional highland house, which typically comprises just one communal room with smoke from a wood fire in the centre of the room [27]. Exposure to environmental tobacco smoke and wood smoke from burning biomass fuel, a popular form of fuel for cooking due to its affordability, may also contribute to high carriage rates by enhancing nasopharyngeal colonization [28], [29]. In an indoor air pollution study, Kirarock recorded significantly higher levels of coarse particulate matter (PM 10 ) released from burning of biofuel in traditional highland houses than in semi-permanent and permanent houses [27].…”
Section: Discussionmentioning
confidence: 99%